Kierunki przemian dydaktyki w naukach o bezpieczeństwie - Andrzej Pieczywok (Historia i Polityka, 2018)
Current times carry a huge load of various events because the 21st century is the century of great changes and huge progress in various spheres of human life. The feeling of security in many environments and social groups diminishes due to development of social and civilization threats. This is why safety education is increasingly important in counteracting various threats. Informing about the kinds of threats and their likelihood, widely understood preventive actions, and rational education in all possible spheres of life – ideally all should be part of teaching safety sciences.